Correlation of religiosity and emotional intelligence among students of Madrasah Aliyah Denpasar - Endy Nurhayati; Cokorda Bagus Jaya Lesmana; Luh Nyoman Alit Aryani (Indoscholar Publication and the Indonesian Psychiatric Association, 2021)
Background: Emotional intelligence is the ability to feel and understand more effectively against emotional sensitivity that includes the ability to motivate oneself or others, self-control, able to understand the feelings of others effectively and able to manage emotions that can be used to guide the mind to make the best decisions. Religiosity is an understanding of religion in a person that is seen through a person's knowledge and beliefs about his religion and is carried out in worship activities. This study aims to determine the correlation between the level of religiosity and emotional intelligence in students of Madrasah Aliyah (MA) in Denpasar. Material and Methods: The participant of this research amounted to 90 students of MA in Denpasar. This study used an observational analytic study with design of cross- sectional study. Measuring the level of religiosity using the scale of Religiosity from Glock & Stark that has been modified in Islam and emotional intelligence is measured using the Emotional Competency Inventory (ECI) scale with a Likert model. Data was analyzed using the SPSS 25.0 program. Results: Level of religiosity 67% with high category and 32,2% with medium category. Emotional intelligence 18,9% with high category and 81,1% with medium category. There is significant mild positive correlation between religiosity and emotional intelligence (r = 0.272; p = 0.010). Conclusion: There is a significant positive mild correlation between the level of religiosity with emotional intelligence.